E2 potentializes benzo(a)pyrene-induced hepatic cytochrome P450 enzyme activities in Nile tilapia at high concentrations - Rodrigues, Aline Cristina Ferreira [UNESP]; Moneró, Tatiana de Oliveira; Frighetto, Rosa Toyoko Shiraishi; Almeida, Eduardo Alves de (Springer, 2014)
In the aquatic environment, biotransformation enzymes are established biomarkers for assessing PAH exposure in fish, but little is known about the effect of 17β-estradiol (E2) on these enzymes during exposure to benzo(a)pyrene (BaP). In this study, Nile tilapia (Oreochromis niloticus) were exposed for 3, 5, and 10 days to BaP (300 μg L(-1)) and E2 (5 μg L(-1)). These substances were applied isolated or mixed. In the mixture experiment, fish were analyzed pre- and postexposure in order to better understand whether preexposure to the hormone masks the responses activated by PAH or vice versa. Phase I enzymes ethoxyresorufin-O-deethylase (EROD), pentoxyresorufin-O-depenthylase (PROD), and benzyloxyresorufin-O-debenzylase (BROD) activities as well as the phase II enzyme glutathione S-transferase (GST) were analyzed. Isolated E2 treatment decreased EROD activity after 3 days, but this enzyme activity returned to control values after 5 and 10 days of exposure. Isolated BaP treatment significantly induced EROD activity after 3 and 5 days, and the activity returned to control levels after ten exposure days. Combined treatment (E2 + Bap) significantly increased EROD activity, both in the pre- and postexposure. This increase was even higher than in the isolated BaP treatment, suggesting a synergism between these two compounds. When E2 and BaP were used singly, they did not change BROD and PROD activities. However, combined treatment (E2 + Bap) significantly increased PROD activity. Isolated BaP treatment increased GST activity after 10 days. However, this response was not observed in the mixture treatment, suggesting that E2 suppressed the GST induction modulated by BaP. The results put together indicated that E2 altered the biotransformation pathway regarding enzymes activated by BaP in Nile tilapia.
Keywords: Oreochromis niloticus; Mixture of contaminants; Benzo(a)pyrene; 17β-Estradiol; Biotransformation enzymes